Assessing volatile organic compounds exposure and chronic obstructive pulmonary diseases in US adults - Lv, Jia-jie; Li, Xin-yu; Shen, Yu-chen; You, Jian-xiong; Wen, Ming-zhe; Wang, Jing-bing; Yang, Xi-tao (Frontiers in Public Health, 2023)
Background: Volatile organic compounds (VOCs) are a large group of chemicals widely used in People's Daily life. There is increasing evidence of the cumulative toxicity of VOCs. However, the association between VOCs and the risk of COPD has not been reported. Objective: We comprehensively evaluated the association between VOCs and COPD. Methods: Our study included a total of 1477 subjects from the National Health and Nutrition Examination Survey, including VOCs, COPD, and other variables in the average US population. Multiple regression models and smooth-curve fitting (penalty splines) were constructed to examine potential associations, and stratified analyses were used to identify high-risk groups. Results: We found a positive association between blood benzene and blood o-xylene concentrations and COPD risk and identified a concentration relationship between the two. That is, when the blood benzene and O-xylene concentrations reached 0.28ng/ml and 0.08ng/ml, respectively, the risk of COPD was the highest. In addition, we found that gender, age, and MET influence the relationship, especially in women, young people, and people with low MET. Significance: This study revealed that blood benzene and blood o-xylene were independently and positively correlated with COPD risk, suggesting that long-term exposure to benzene and O-xylene may cause pulmonary diseases, and providing a new standard of related blood VOCs concentration for the prevention of COPD.